Method for producing regenerated water absorptive resin composition

JP2025025616APending Publication Date: 2025-02-21NIPPON SHOKUBAI CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023130519
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0018】 本発明によって、残存分解剤量を低く制御(1000ppm以下、100ppm以下)に制御することで、吸水性樹脂の生産(特に重合)や物性が安定し、着色も低減できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025616000001
    Figure 2025025616000001
Patent Text Reader

Abstract

To provide a water absorptive resin in which physical properties and production are stable and coloration is little, while using a decomposed product of a used water absorptive resin as a part of a raw material.SOLUTION: A method for producing a regenerated water absorptive resin composition includes a step of polymerizing a monomer aqueous solution, and a step of drying a water-containing gel-like crosslinked polymer after polymerization, makes 50 mass% or more of a water absorptive resin soluble by a decomposer, and uses an aqueous solution of the obtained solubilized polymer as a part of a raw material, wherein a mass average molecular weight (Mw) of the solubilized polymer is 30,000 or more, and an amount of the decomposer remaining in the aqueous solution of the solubilized polymer is 1,000 ppm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a recycled water-absorbent resin composition using a solubilized water-absorbent resin (a decomposition product of a water-absorbent resin) as a part or all of a raw material. [Background technology]

[0002] In recent years, water-absorbent resins have been widely used as constituent materials for absorbent articles such as paper diapers, sanitary napkins, incontinence pads, absorbent sheets, cat litter, etc., from the viewpoint of absorbing body fluids. Although absorbent articles, which are the main application of water-absorbent resins, are generally disposable, there has been growing interest in recycling sanitary products due to the increasing environmental awareness.

[0003] One proposed method for recycling used sanitary products (for example, paper diapers that have absorbed human waste) involves collecting the used sanitary products, separating them into their component parts such as pulp, nonwoven fabric, adhesive, and water-absorbent resin, and then washing, refining, sterilizing, and bleaching them before recycling.

[0004] Among these components, water-absorbent resins swell by absorbing the cleaning water and sterilizing water in the recycling process, and the urine contained in the cleaning water in the cleaning process, so they need to be washed and dried before they can be reused as products, and it is known that they deteriorate and become discolored due to the heat during drying. For this reason, recycling water-absorbent resins has been technically difficult.

[0005] Conventionally, technology has been proposed to solubilize used water-absorbent resin with a decomposing agent in order to recover pulp, nonwoven fabric, adhesives, etc. from sanitary products. However, since water-absorbent resin is difficult to recycle or separate, it has generally been solubilized to separate the pulp, etc., and then disposed of.

[0006] However, in recent years, a technology has been developed for separating and regenerating used water-absorbent resins for use in absorbent articles, and recycling them into water-absorbent resins or other useful substances (e.g., water-soluble polymers and adhesives).

[0007] As a method for recycling used water-absorbent resin, a method has been proposed in which the used water-absorbent resin is separated from used absorbent articles (particularly sanitary products such as paper diapers), purified, and reused (Patent Documents 1 to 3).

[0008] A recycled water absorbent resin composition obtained from a used water absorbent resin is reused as a water absorbent resin as it is. However, since a performance of a recycled water absorbent resin composition is generally deteriorated in a recycling process, the use of the recycled water absorbent resin composition is actually limited.

[0009] In view of this, as applications of the recycled water absorbent resin composition, which is likely to be accompanied by a decrease in performance due to recycling, methods have been proposed in which the recycled water absorbent resin composition is used as a raw material for the water absorbent resin (Patent Document 6) or a solubilized matter of used water absorbent resin is used as a raw material for the water absorbent resin (Patent Documents 4, 7 to 12), thereby reducing the raw material used for the water absorbent resin and restoring the performance of the recycled water absorbent resin composition.

[0010] However, in the method of using a solubilized product of a used water absorbent resin as a part of the raw material of a water absorbent resin in addition to a normal monomer component as a raw material of the water absorbent resin (Patent Documents 4, 7 to 11, etc.), there occurs coloring and a decrease in performance due to impurities remaining in the used water absorbent resin, and further, there is a drawback that the productivity becomes unstable.

[0011] Many recycling methods for used water absorbent resins have been proposed, including Patent Documents 1 to 11. However, there are significant limitations to using a recycled water absorbent resin composition as a water absorbent resin or to using a used water absorbent resin or a solubilized product thereof as a raw material for a water absorbent resin. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] International Publication No. WO2019 / 087485 [Patent Document 2] International Publication No. WO2019 / 151538 [Patent Document 3] International Publication No. WO2021 / 075506 [Patent Document 4] International Publication No. WO2020 / 241025 [Patent Document 5] International Publication No. WO2021 / 205780 [Patent Document 6] International Publication No. WO2021 / 044690 [Patent Document 7] International Publication No. WO2020 / 213298 [Patent Document 8] International Publication No. WO2022 / 080342 [Patent Document 9] International Publication No. WO2022 / 081523 [Patent Document 10] International Publication No. WO2022 / 082163 [Patent Document 11] International Publication No. WO2022 / 082165 [Patent Document 12] JP 2023-038963 A Summary of the Invention [Problem to be solved by the invention]

[0013] The present invention provides a method for producing a recycled water-absorbent resin composition that has stable physical properties and stable production and is less colored, while using a solubilized (decomposed) product of used water-absorbent resin.

[0014] While various recycling methods for used water absorbent resins have been proposed in the past, the present inventors have focused on the remaining decomposition agent for the first time in a method of using a solubilized product of used water absorbent resin as a part of a raw material for a water absorbent resin, and solved the above-mentioned problems (coloration, fluctuations in physical properties, and particularly fluctuations in polymerization time) by "(1) using a solubilized product having a residual decomposition agent of 1000 ppm or less after decomposition treatment (first method)" or "(2) using a solubilized product after a decomposition agent reduction treatment that has been performed on the solubilized product after decomposition treatment to reduce the amount of residual decomposition agent (second method)". [Means for solving the problem]

[0015] The present inventors have conducted intensive research to solve the above problems. As a result, they have found that the above problems can be solved by focusing on a residual decomposition agent for the first time and performing a specific residual treatment when producing a recycled water absorbent resin composition using a used water absorbent resin or a solubilized product thereof as a part of a raw material, and have completed the present invention.

[0016] That is, the present invention (first invention) is a method for producing a recycled water-absorbent resin composition, comprising a step of polymerizing an aqueous monomer solution and a step of drying a hydrogel-like crosslinked polymer after polymerization, in which 50 mass % or more of the water-absorbent resin is solubilized by a decomposing agent, and the obtained aqueous solution of the solubilized polymer is used as a part of a raw material, The mass average molecular weight (Mw) of the solubilizing polymer is 30,000 or more, and The present invention provides a method for producing a recycled water-absorbent resin composition, in which the amount of decomposition agent remaining in the aqueous solution of the solubilized polymer is 1000 ppm or less.

[0017] In addition, as a second invention, A method for producing a recycled water-absorbent resin composition, comprising a step of polymerizing an aqueous monomer solution and a step of drying a hydrogel-like crosslinked polymer after polymerization, in which 50% by mass or more of the water-absorbent resin is solubilized by a decomposing agent, and the aqueous solution of the solubilized polymer obtained is used as a part of a raw material, The present invention provides a method for producing a regenerated water-absorbent resin composition, in which the solubilized polymer has a mass average molecular weight (Mw) of 30,000 or more after a treatment for reducing the amount of decomposing agent remaining in the aqueous solution of the solubilized polymer is carried out. Effect of the Invention

[0018] According to the present invention, by controlling the amount of remaining decomposition agent to a low level (1000 ppm or less, 100 ppm or less), the production (particularly polymerization) and physical properties of the water absorbent resin are stabilized, and coloring can also be reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention is characterized in that, in a manufacturing method for a recycled water absorbent resin composition in which a solubilized material of a used water absorbent resin is used as a part of a raw material of a water absorbent resin, attention is focused for the first time on a residual decomposition agent, and that "(1) a solubilized material having a residual decomposition agent of 1000 ppm or less after a decomposition treatment is used (first method)" or "(2) a solubilized material after a decomposition agent reduction treatment is performed on the solubilized material after a decomposition agent reduction treatment is used (second method)".

[0020] Each of the configurations will be described below.

[0021] (1) Raw materials other than the monomer components of the recycled water absorbent resin composition according to the present invention The present invention is a method for producing a recycled water absorbent resin composition using a solubilized product of a used water absorbent resin as a part of a raw material. In the production method of the present invention, a solubilized product of a used water absorbent resin in which a residual decomposition agent is controlled to a low level, more preferably a chelating agent and a reducing agent, are used as raw materials other than a monomer component.

[0022] (Used water-absorbent resin) The present invention is a method for producing a recycled water absorbent resin composition using a solubilized product of used water absorbent resin as part of the raw material. In the present invention, the water absorbent resin is solubilized, and preferably used water absorbent resin is solubilized.

[0023] In the present invention, the "used water absorbent resin" means a water absorbent resin contained in an absorbent article that has been processed by a user of the water absorbent resin after shipment from a water absorbent resin factory; an absorbent article that has been sold and distributed and used by a consumer; or an absorbent article that has been discarded after use.

[0024] Specifically, the used water-absorbent resin may be a water-absorbent resin used in sanitary products such as paper diapers. In addition, the used water-absorbent resin may include a waste water-absorbent resin generated in the manufacturing process of the water-absorbent resin, or a water-absorbent resin contained in an absorbent article that has been discarded before use.

[0025] In the present invention, the used water absorbent resin is preferably a water absorbent resin after absorption, such as a paper diaper. Since such a water absorbent resin absorbs and swells with urine, the swollen water-containing gel of urine, etc. is washed, dehydrated, and sterilized as necessary to obtain a water-containing gel of the used water absorbent resin after purification. The washing, dehydration, and sterilization method for the absorbed water can be appropriately selected from Patent Documents 1 to 3 and other known recycling methods, such as WO2021 / 162082, WO2022 / 091975, WO2023 / 007871, WO92 / 007995, JP 2013-150977, and JP 2003-326161, and is not particularly limited as long as a water-containing gel of the used water absorbent resin after purification can be obtained. The solid content of the hydrogel is from 1% by mass to 95% by mass, and further from 10% by mass to 90% by mass, and the swelling may be water or a mixed solvent of water and a hydrophilic organic solvent.

[0026] (Solubilized material of used water absorbent resin) Regarding the used water absorbent resin, the hydrogel after or before purification is solubilized by the methods described in Patent Documents 4 to 8 or other known decomposition methods, for example, JP-A-6-313008 (persulfate), JP-A-4-317784 (heat treatment at 40 ° C. in the presence of an oxidizing agent), JP-A-5-247307 (ascorbic acid), JP-A-2001-316519 (periodate), JP-A-09-249711 (acid or alkali), JP-A-2020-116569 (water-soluble reducing agent and iron ion and / or copper ion), etc., and the solubilized product of the water absorbent resin is obtained. It is not particularly limited.

[0027] The solid content of the hydrogel is 1% by mass or more and 95% by mass or less, and further 10% by mass or more and 90% by mass or less, and the swelling may be water or a mixed solvent of water and a hydrophilic organic solvent. The solubilization rate (%) of the water-absorbent resin after the decomposition treatment is preferably high, and the water-soluble content as specified in EDANA470.2-02 (2002) is 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, and particularly substantially 100% by mass is considered to be solubilized. If the solubilization rate is low, the applications of the resin as both a water-absorbent resin and a water-soluble resin are limited, and especially when the resin is used as a raw material for a water-absorbent resin, the performance (e.g., water absorption ratio) of the obtained water-absorbent resin may be reduced.

[0028] In one embodiment of the present invention, the range of the mass average molecular weight of the solubilized polymer obtained by decomposing the used water absorbent resin is 30,000 or more, preferably 30,000 to 1,000,000, more preferably 40,000 to 800,000, and even more preferably 50,000 to 600,000. If the mass average molecular weight is too low, the water-soluble content of the water absorbent resin produced using the solubilized polymer as a part of the raw material may increase, or the water absorption properties may decrease. If the mass average molecular weight is too large, the viscosity of the solubilized polymer aqueous solution may increase, and the handleability may decrease.

[0029] In one embodiment of the present invention, the YI value of the solubilized polymer aqueous solution (containing 10% by mass or more and 40% by mass or less of the solubilized polymer) obtained by decomposing the water absorbent resin is preferably 15 or less, more preferably 13 or less, further preferably 11 or less, and most preferably 10 or less. If the YI value is more than 15, there is a risk that the water absorbent resin will be excessively colored when recycled to the production process of the water absorbent resin.

[0030] (Decomposer) In the present invention, an oxidizing agent or a reducing agent is used as the decomposing agent.

[0031] Examples of oxidizing agents that can be used as decomposition agents include persulfates, peroxides, and hypochlorous acid. Examples of peroxides include hydrogen peroxide and alkyl hydroperoxides. Examples of persulfates include sodium persulfate, potassium persulfate, and ammonium persulfate. Examples of hypochlorites include sodium hypochlorite (NaClO), calcium hypochlorite (Ca(ClO)2), and potassium hypochlorite (KClO).

[0032] Examples of the reducing agent include sulfurous acid (salt), hydrogen sulfite (salt), phosphorous acid (salt), hypophosphorous acid (salt), thiosulfuric acid (salt), formic acid, oxalic acid, erythorbic acid, amines, ascorbic acid (salt) or derivatives thereof (e.g., L-ascorbic acid (salt), isoascorbic acid (salt), and alkyl esters of ascorbic acid), phosphate esters, and sulfate esters. Of these, sulfurous acid (salt), hydrogen sulfite (salt), L-ascorbic acid (salt), and isoascorbic acid (salt) are preferably used.

[0033] In addition to the oxidizing agent and the reducing agent, a transition metal ion may be used in combination. Specific examples of the transition metal ion include Cu. 2+ , Ag + , Fe 2+ , Fe 3+ , Al 3+ , Ni 2+ , Mn 2+ and the like, and preferably, iron ions (Fe 2+ ), copper ions (Cu 2+ ), and most preferably iron ions (Fe 2+ ) Examples of compounds that generate the aforementioned transition metal ions include chlorides and hydrates thereof, such as ferrous chloride, organic acid salts and hydrates thereof, such as ferrous fumarate, ferrous oxalate, ferrous chloride, sodium ferrous citrate, ferrous gluconate, ferrous citrate, ferrous acetate, and sulfates and hydrates thereof, such as ferrous sulfate, and the like.

[0034] Among these decomposing agents, oxidizing agents are preferred from the viewpoints of decomposition efficiency and performance of the water-absorbing resin, and hydrogen peroxide is more preferred.

[0035] The amount of the decomposition agent is preferably 0.1 to 50 parts by mass, more preferably 0.3 to 30 parts by mass, and even more preferably 0.5 to 20 parts by mass, relative to 100 parts by mass of the water absorbent resin. If the amount of the decomposition agent is too small, the decomposition property may decrease. If the amount of the decomposition agent is too large, the solubilized polymer may become colored.

[0036] When the solubilized polymer obtained by the solubilization treatment (decomposition) or its aqueous solution is added, the amount of the oxidizing agent remaining in the solubilized polymer or its aqueous solution may be measured in advance by a method such as redox titration or ion chromatography to determine the content of the oxidizing agent contained in the solubilized polymer, and conditions such as the amount of initiator used in the "polymerization step" (when an oxidizing agent is used as an initiator, the amount of the oxidizing agent other than the oxidizing agent contained in the solubilized polymer) and the starting temperature may be adjusted based on the amount. In the production of the water absorbent resin, a step after the polymerization step may further include a step of adding an oxidizing agent other than the oxidizing agent contained in the solubilized polymer. In other words, based on the content of the oxidizing agent in the solubilized polymer, the amount of the oxidizing agent other than the oxidizing agent contained in the solubilized polymer to be added may be determined and used as an initiator used in the polymerization step and / or as an additive to be mixed in a step after the polymerization step.

[0037] (Amount of decomposition agent remaining after solubilization) In the production method of the present invention (first method, more preferably second method), the amount of residual decomposition agent after decomposition treatment is controlled to 1000 ppm or less. More preferably, the amount is 800 ppm or less, 600 ppm or less, 400 ppm or less, 200 ppm or less, 100 ppm or less, 40 ppm or less, 20 ppm or less, and 10 ppm or less (below detection limit), in that order. If the amount of the residual agent is large, in a production method of a recycled water absorbent resin composition in which a solubilized polymer of a used water absorbent resin is used as a part of the raw material of the water absorbent resin, polymerization becomes unstable, and deterioration or fluctuation in performance is observed, which is not preferable.

[0038] (Reduction rate of decomposition agent after solubilization) In the production method of the present invention, the decomposition agent is consumed at a rate of preferably 50% by mass or more, further 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more of the amount used. In the present invention, a certain amount or more of the decomposition agent is used to rapidly carry out the decomposition treatment, and the decomposition agent is reacted sufficiently or the remaining decomposition agent is decomposed to reduce the concentration to 1000 ppm or less.

[0039] (Decomposition agent reduction rate)=(Remaining decomposition agent of solubilized material used in the manufacturing process of water absorbent resin) / (Amount of decomposition agent used for solubilization)×100

[0040] The reduction rate of the decomposing agent can be appropriately adjusted by the type of the decomposing agent and the decomposition conditions (temperature, time, concentration, pH, etc.), and it is preferable to set the amount of the remaining decomposing agent to the above amount.

[0041] (Decomposition temperature during solubilization treatment) In one embodiment of the present invention, the temperature at which the water-absorbent resin is decomposed is 40°C to 195°C, preferably 50°C to 130°C, more preferably 65°C to 120°C, and even more preferably 80°C to 110°C. By increasing the temperature, the amount of radicals generated from the decomposing agent increases, and the time required to obtain a solubilized polymer can be shortened. However, if the temperature is increased too much, the generated radicals may be deactivated before the water-absorbent resin is decomposed. As a method for adjusting the decomposition temperature, the above-mentioned mixing may be carried out at room temperature, and then the container may be placed at a predetermined temperature (a container filled with the mixture may be immersed in an oil bath at a predetermined temperature). Alternatively, the above-mentioned mixing may be carried out in a predetermined temperature atmosphere, and then the container may be left in that temperature atmosphere.

[0042] (Solubilization treatment concentration) The solubilization treatment of the water-absorbent resin is preferably carried out in an aqueous solution, i.e., a hydrogel, and the concentration is appropriately determined. The solubilization treatment is carried out in a hydrogel having a water-absorbent resin concentration of 1% by mass or more and 90% by mass or less, 2% by mass or more and 80% by mass or less, 5% by mass or more and 60% by mass or less, further 10% by mass or more and 40% by mass or less, 15% by mass or more and 35% by mass or less, or 20% by mass or more and 30% by mass or less, and preferably the above-mentioned heat treatment is carried out. When the water-absorbent resin is in a hydrogel state, such as a state in which the water-absorbent resin is contained in a used absorbent article, the water absorbed in the water-absorbent resin may be used as it is. If the water absorbed in the water-absorbent resin does not reach the desired concentration (ratio), water may be added to adjust it.

[0043] (Residual decomposition agent reduction treatment) In the manufacturing method of the present invention (the second method, preferably the first method), a treatment for reducing the residual decomposition agent is carried out after the decomposition treatment. As a method for reducing the residual decomposition agent, a method for aging the solubilized polymer after the solubilization treatment for a predetermined time or more, further at a predetermined temperature and for a predetermined time or more (aging after the solubilization treatment), or a method for decomposing the polymer by adding an acid or alkali after the solubilization treatment may be used. Here, the solubilization treatment of the water absorbent resin and the treatment for reducing the residual decomposition agent are solubilization treatment when the solubilization treatment of the water absorbent resin mainly proceeds, and are reduction treatment of the residual decomposition agent when the reduction of the residual decomposition agent mainly proceeds after the solubilization treatment, but when the solubilization treatment and the reduction treatment of the residual decomposition agent are carried out in different devices, for example, when the residual decomposition agent is reduced in a different device or storage tank after the solubilization treatment, that is, when different reactors are used for the solubilization treatment and the reduction treatment of the residual decomposition agent, the two can be clearly distinguished.

[0044] This is achieved by treating the solubilized polymer after the solubilization treatment for a predetermined time or more, and further at a predetermined temperature and for a predetermined time or more. The temperature and time are appropriately determined depending on the type and amount of the remaining decomposition agent, and are usually determined appropriately for 10 minutes or more, further 10 minutes to 240 minutes, 15 minutes to 120 minutes, 20 minutes to 100 minutes, etc. The temperature after the solubilization treatment is 40°C or more, preferably 50°C or more, further 60°C or more, 70°C or more. In terms of effect and energy, the upper limit may be 110°C or less, 100°C or less, or 90°C or less. To reach the predetermined temperature, the solubilized polymer after the solubilization treatment may be heated, and when the solubilization treatment is performed by heating, the solubilized polymer after the solubilization treatment may be kept warm or cooled to a predetermined temperature and then kept warm or heated.

[0045] Another method for reducing the amount of residual decomposition agent is to add an acid or alkali to reduce the amount of residual decomposition agent after the solubilization of the aqueous resin. The type and amount of the acid or base are appropriately determined depending on the type and amount of the residual decomposition agent, and are usually appropriately determined to be 0.001% by mass or more and 100% by mass or less, further 0.01% by mass or more and 50% by mass or less, or 0.1% by mass or more and 25% by mass or less, relative to the solubilized material. Examples of the acid used include inorganic acids such as hydrochloric acid, sulfuric acid, and phosphoric acid, and organic carboxylic acids such as acetic acid, malic acid, and citric acid, and examples of the base include carbonates (hydrogen) salts of alkali metals such as sodium carbonate and sodium hydrogen carbonate, and alkali metal hydroxides such as caustic soda and caustic potash.

[0046] (Residual urea amount) Preferably, by carrying out a urea removal treatment such as washing, impurities derived from human waste contained in the water absorbent resin can be reduced, and thus coloration of the regenerated water absorbent resin can be reduced.

[0047] Among the impurities derived from human waste, the residual amount of urea, which has a high content and / or content, is set to 4% by mass or less, 3% by mass or less, 2% by mass or less, preferably 1.8% by mass or less, more preferably 1.6% by mass or less, thereby preventing the deterioration of the water absorption performance of the water absorbent resin and reducing coloration. The lower the lower limit, the more preferable it is, but in the method of the present invention, even if some residual monomer remains (for example, 0.01% by mass or even 0.1% by mass), it is possible to obtain a recycled water absorbent resin composition with little coloration and little residual monomer without excessive purification. Excessive purification not only increases the cost of regeneration and deteriorates the recycled water absorbent resin composition, but is also undesirable from the viewpoint of the consumed resources and energy, and from the balance between the recycled resources and the consumed resources involved in regeneration. However, the present invention has the advantage that such excessive purification is not required.

[0048] The method for quantifying the amount of urea remaining in the water absorbent resin is not particularly limited as long as it can quantify urea. For example, a method in which the water absorbent resin is dispersed in water, the urea contained in the water absorbent resin is extracted into a water layer, and then the urea contained in the water layer is directly quantified by liquid chromatography, gas chromatography, or the like can be mentioned. In addition, a method in which urea is quantified by a colorimetric method such as the urease indophenol method or the diacetyl monoxime method can be mentioned. The method for reducing urea may be performed by washing or dehydrating the used water absorbent resin with reference to

[0025] to

[0035] of PCT / JP2023 / 003773 and its examples and comparative examples, and the like, to reduce urea from the used water absorbent resin to a desired range. In the present invention, it is preferable because a white regenerated water absorbent resin composition can be obtained without excessively purifying the used water absorbent resin.

[0049] (Temperature of solubilized polymer during mixing) In order to solve the problems of the present invention, it is preferable that the solubilized polymer is preheated from the viewpoint of uniform mixing and stable production. The solubilized polymer is preheated to 40°C or higher, preferably 50°C or higher, further 60°C or higher, or 70°C or higher. In terms of effect and energy, the upper limit may be 110°C or lower, 100°C or lower, or 90°C or lower. The temperature of the hydrogel may be appropriately adjusted by the polymerization temperature, aging after polymerization, heating or cooling. Excessively high temperatures may cause coloring of the obtained water-absorbent resin.

[0050] (chelating agent) When the solubilized material is used in the manufacturing process of the water absorbent resin, it is preferable that a chelating agent is further present in the present invention. With this configuration, coloration and performance deterioration resulting from the recycled water absorbent resin composition are further suppressed. The chelating agent is preferably contained in the hydrogel before drying, and the chelating agent may be added to the used water absorbent resin or its decomposition product, or the chelating agent may be added to the monomer in the polymerization step of the recycled water absorbent resin composition using the used water absorbent resin or its decomposition product as a raw material, or to the hydrogel after polymerization. When the chelating agent is added after polymerization, it is also preferable to mix the chelating agent with the hydrogel before drying and mix the chelating agent uniformly by gel grinding.

[0051] The chelating agent to be used is preferably a polymeric compound or a non-polymeric compound, more preferably a non-polymeric compound, and is preferably a chelating agent containing an element other than carbon, hydrogen, and oxygen, more preferably nitrogen or phosphorus, in the molecule.

[0052] Specific examples of the chelating agent used in the present invention include hydroxy polycarboxylic acids, amino polycarboxylic acids, organic polyphosphates, inorganic polyphosphates, amino polyphosphates, and tropolone derivatives. At least one compound selected from the group consisting of these compounds is applied in the present invention. The above-mentioned "polyvalent" refers to having multiple functional groups in one molecule, preferably 2 to 30 functional groups, more preferably 3 to 20 functional groups, and even more preferably 4 to 10 functional groups.

[0053] From the viewpoint of the effect on polymerization and the physical properties of the resulting recycled water absorbent resin composition, the molecular weight of the chelating agent is preferably from 100 to 5000, more preferably from 200 to 1000. If the molecular weight exceeds 5000, the aqueous monomer solution may thicken depending on the timing of addition of the chelating agent, which is undesirable because it makes it difficult to control polymerization and mix uniformly.

[0054] Specific examples of the amino polycarboxylic acid include iminodiacetic acid, hydroxyethyliminodiacetic acid, nitrilotriacetic acid, nitrilotripropionic acid, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, N,N-bis(2-hydroxyethyl)glycine, diaminopropanoltetraacetic acid, ethylenediamine2propionic acid, N-hydroxyethylethylenediaminetriacetic acid, glycol ether diaminetetraacetic acid, diaminopropanetetraacetic acid, N,N'-bis(2-hydroxybenzyl)ethylenediamine-N,N'-diacetic acid, 1,6-hexamethylenediamine-N,N,N',N'-tetraacetic acid, and salts thereof.

[0055] Specific examples of the organic polyphosphate include nitriloacetic acid-di(methylenephosphinic acid), nitrilodiacetic acid-(methylenephosphinic acid), nitriloacetic acid-β-propionic acid-methylenephosphonic acid, nitrilotris(methylenephosphonic acid), and 1-hydroxyethylidene diphosphonic acid.

[0056] Specific examples of the inorganic polyphosphate include pyrophosphoric acid, tripolyphosphoric acid, and salts thereof.

[0057] Specific examples of the hydroxy polyvalent carboxylic acid include malic acid, citric acid, and salts thereof.

[0058] Specific examples of the amino polyphosphate include ethylenediamine-N,N'-di(methylenephosphinic acid), ethylenediaminetetra(methylenephosphinic acid), cyclohexanediaminetetra(methylenephosphonic acid), ethylenediamine-N,N'-diacetic acid-N,N'-di(methylenephosphonic acid), ethylenediamine-N,N'-di(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), polymethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), and salts thereof.

[0059] Specific examples of the tropolone derivative include tropolone, β-thujaplicin, and γ-thujaplicin.

[0060] Among these, chelating agents selected from amino polycarboxylic acids, organic polyphosphates, and amino polyphosphates are preferred, amino polycarboxylic acid-based chelating agents having three or more carboxyl groups are more preferred, and from the viewpoint of gel stability, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, and salts thereof are even more preferred.

[0061] In the present invention, the content (amount used) of the chelating agent is 0.001 parts by mass or more and 5 parts by mass or less, preferably 0.02 parts by mass or more and 1 part by mass or less, more preferably 0.03 parts by mass or more and 0.9 parts by mass or less, even more preferably 0.04 parts by mass or more and 0.8 parts by mass or less, still more preferably 0.05 parts by mass or more and 0.7 parts by mass or less, particularly preferably 0.06 parts by mass or more and 0.6 parts by mass or less, and most preferably 0.07 parts by mass or more and 0.5 parts by mass or less, relative to 100 parts by mass of the solid content of the water absorbent resin.

[0062] (reducing agent) When the solubilized material is used in the manufacturing process of the regenerated water absorbent resin composition, it is preferable to further add a reducing agent, particularly a sulfur-based inorganic or organic reducing agent, during or after the drying process. This configuration further suppresses coloration and performance deterioration of the regenerated water absorbent resin composition. In addition, the by-production of impurity acrylamide in the regenerated water absorbent resin composition can also be suppressed. The reducing agent is preferably contained in a hydrogel before drying, and the reducing agent may be added to a used water absorbent resin or its decomposition product, or the reducing agent may be added to a hydrogel after polymerization obtained in a polymerization process of a regenerated water absorbent resin composition using a used water absorbent resin or its decomposition product as a raw material. When a reducing agent is added after polymerization, it is also preferable to mix the reducing agent with the hydrogel before drying and mix the reducing agent uniformly by gel crushing.

[0063] The reducing agent is preferably a sulfur-based inorganic or organic reducing agent, and examples of such reducing agents include inorganic reducing agents such as sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, sulfurous acid, sodium hydrogen sulfite, potassium hydrogen sulfite, ammonium hydrogen sulfite, sodium thiosulfate, potassium thiosulfate, ammonium thiosulfate, and magnesium thiosulfate, and organic reducing agents such as 2-hydroxy-2-sulfinatoacetic acid, 2-hydroxy-2-sulfonatoacetic acid, cysteine, and cystine, and one or more of these can be used. Among these, sulfites and hydrogen sulfites are preferred in terms of effectiveness and cost.

[0064] In addition, the amount of the sulfur-containing reducing agent is preferably 0.05 parts by mass or more and 10 parts by mass or less, and preferably 0.1 parts by mass or more and 8 parts by mass or less, relative to 100 parts by mass of the water absorbent resin. If the amount of the sulfur-containing reducing agent used is less than the lower limit of 0.05 parts by mass, the desired effect of reducing the residual monomer may not be obtained, and if the amount exceeds the upper limit of 10 parts by mass, the amount added becomes excessive for the required effect of reducing the residual monomer, which may lead to a decrease in physical properties, and is uneconomical in terms of cost. In addition, the additive containing the sulfur-containing reducing agent is preferably 0.001% by mass or more and 50% by mass or less relative to the aqueous solution. In the present invention, the additive is selectively and preferentially added to the surface of the particles and the fine particles, so a small amount is sufficient and the physical properties are not decreased.

[0065] (Surfactant) When the solubilized material is used in the manufacturing process of the water absorbent resin, a surfactant is preferably used. Examples of the surfactant include anionic, cationic, nonionic, and amphoteric surfactants, and low molecular weight or high molecular weight surfactants thereof, polymer lubricants, etc. By using the surfactant, the fluidity of the gel is improved and mixing becomes easier.

[0066] The amount of the surfactant added is appropriately set depending on the water content of the hydrogel or particulate hydrogel and the type of gel fluidizer, and is preferably 0.001% by mass or more and 0.5% by mass or less, more preferably 0.01% by mass or more and 0.3% by mass or less, and even more preferably 0.02% by mass or more and 0.2% by mass or less, based on the solid content of the hydrogel.

[0067] (2) Method for producing recycled water-absorbent resin composition As a method for producing a recycled water absorbent resin composition using a solubilized product of used water absorbent resin as a part of a raw material,

[0068] (A) As in Patent Documents 4, 7 to 11, a method for producing a recycled water absorbent resin composition may be used in which a solubilized product (solubilized polymer) of a water absorbent resin obtained by separating and solubilizing a used water absorbent resin from a used article (e.g., a used sanitary product) is applied to a production process of a water absorbent resin (e.g., mixing a solubilized product of a water absorbent resin in a polymerization process),

[0069] (B) A method for producing a recycled water-absorbent resin composition in which a used water-absorbent resin is separated from a used item (e.g., a used sanitary product) and a solubilized product (solubilized polymer) of the water-absorbent resin is re-crosslinked (e.g., JP 2020-049398 A).

[0070] Below, we will discuss (A).

[0071] In one embodiment of the present invention, the method for producing a water-absorbent resin using a solubilized polymer obtained by decomposing a water-absorbent resin as a raw material is a production method in which the solubilized polymer obtained by decomposing a water-absorbent resin is used as a raw material in any one of the steps of preparing an aqueous monomer solution, the polymerization step, the hydrogel crushing step, the drying step, the surface cross-linking step, and the granulation step when newly producing a water-absorbent resin (producing a conventional water-absorbent resin using a monomer constituting a water-absorbent resin as a raw material).

[0072] (Time of addition of solubilizing polymer, amount added, temperature added, other additives used) The method of adding the solubilized polymer includes adding it as an aqueous solution, adding it as a powder after drying, and adding it as an aqueous dispersion (slurry) with some undissolved matter remaining. These may be added alone or in combination. From an economical point of view, it is preferable to use the aqueous solution (aqueous dispersion) of the solubilized polymer obtained by the solubilization treatment (decomposition) of the used water absorbent resin as it is.

[0073] (1) Addition of solubilizing polymer to monomer during polymerization (2) Addition of a solubilizing polymer to a monomer during polymerization or to a hydrogel during polymerization (3) Addition of solubilizing polymer to hydrogel during gel grinding (4) Addition of solubilizing polymer to hydrogel during drying (5) Addition of solubilizing polymer to water-absorbent resin during surface cross-linking (6) Addition of solubilized polymer to water absorbent resin or water absorbent resin fine powder in the granulation process Among these (1) to (6), it is preferable to add the solubilizing polymer in any step prior to the drying step. By adding the solubilizing polymer in any step, the solubilizing polymer is not only uniformly dispersed in the resin, but also has a high probability of being incorporated into the resin, making it difficult to escape from the resin, and the water-soluble content of the resin is reduced.

[0074] The proportion of the solubilized polymer as a raw material in the entire water absorbent resin raw material is 1% by mass to 60% by mass, preferably 3% by mass to 50% by mass, more preferably 5% by mass to 40% by mass. In other words, the solubilized polymer is preferably used as a raw material in an amount of 1% by mass to 60% by mass, more preferably 3% by mass to 50% by mass, more preferably 5% by mass to 40% by mass, based on the entire water absorbent resin raw material.

[0075] The solubilized polymer is preferably heated as described above after the residual decomposition agent is reduced as described above. More preferably, a chelating agent and / or a reducing agent is used and coexists with the solubilized polymer to produce a water-absorbing resin.

[0076] According to the method for producing a recycled water-absorbent resin composition in one embodiment of the present invention, it is possible to produce a water-absorbent resin with little deterioration in water-absorbing performance and little coloring due to the added solubilizing polymer.

[0077] A method for producing a water-absorbent resin using a solubilized water-absorbent resin as part of the raw material will be described below.

[0078] (2-1) Preparation of monomer aqueous solution (monomer) As the monomer, a wide variety of monomers used in water absorbent resins can be used, but a representative example is a step of preparing an aqueous solution containing acrylic acid as a main component (hereinafter referred to as "monomer aqueous solution"). A monomer slurry liquid can also be used within a range in which the water absorption performance of the resulting water absorbent resin is not reduced, but for the sake of convenience, an aqueous monomer solution will be described in this section. This means that the amount (content) of acrylic acid (salt) used is usually 50 mol % or more, preferably 70 mol % or more, and more preferably 90 mol % or more (upper limit 100 mol %) relative to the total monomers (excluding internal crosslinking agents) used in the polymerization reaction of the water absorbent resin.

[0079] The monomer other than acrylic acid may be any compound that can be polymerized to become a water-absorbent resin. Examples of the unsaturated monomers include methacrylic acid, (anhydrous) maleic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, and 2-hydroxyethyl (meth)acryloyl phosphate; amide group-containing unsaturated monomers such as (meth)acrylamide, N-ethyl (meth)acrylamide, and N,N-dimethyl (meth)acrylamide; amino group-containing unsaturated monomers such as N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylamide; mercapto group-containing unsaturated monomers; phenolic hydroxyl group-containing unsaturated monomers; and lactam group-containing unsaturated monomers such as N-vinylpyrrolidone.

[0080] From the viewpoint of the water absorption performance of the resulting water absorbent resin, the monomer other than acrylic acid is an acid group-containing unsaturated monomer, more preferably methacrylic acid, maleic acid (anhydride), itaconic acid, cinnamic acid, and even more preferably methacrylic acid.

[0081] In the case where an acid group-containing unsaturated monomer having an acid group such as a carboxyl group is used among acrylic acid and the above-mentioned monomers, it is more preferably an alkali metal salt, even more preferably at least one selected from the group consisting of sodium salts, lithium salts and potassium salts, and particularly preferably a sodium salt.

[0082] From the viewpoint of water absorption performance, the number of moles of the neutralization salt relative to the total number of moles of the acid group-containing unsaturated monomer and its neutralization salt (hereinafter referred to as "neutralization rate") is preferably 40 mol% or more, more preferably 40 mol% to 80 mol%, even more preferably 45 mol% to 78 mol%, and particularly preferably 50 mol% to 75 mol%. The adjustment of the neutralization rate may be performed before the start of the polymerization reaction of the acid group-containing unsaturated monomer, during the polymerization reaction of the acid group-containing unsaturated monomer, or on the hydrogel-like crosslinked polymer obtained after the completion of the polymerization reaction of the acid group-containing unsaturated monomer. In addition, the neutralization rate may be adjusted by selecting one of the stages before the start of the polymerization reaction, during the polymerization reaction, or after the completion of the polymerization reaction, or the neutralization rate may be adjusted at multiple stages.

[0083] (Internal crosslinking agent) In the production method of the present invention, an internal crosslinking agent is preferably used, which adjusts the water absorption performance and gel strength of the resulting recycled water absorbent resin composition upon water absorption.

[0084] The internal crosslinking agent may have a total of two or more unsaturated bonds or reactive functional groups in one molecule. For example, N,N-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, ethylene glycol diglycidyl ether, glycidyl (meth)acrylate, etc. may be mentioned. Among these, two or more may be used in combination. The amount of the internal crosslinking agent used is preferably 0.001 mol% or more and 5 mol% or less, more preferably 0.005 mol% or more and 2 mol% or less, based on the monomer.

[0085] (Other additives) In one embodiment of the present invention, from the viewpoint of improving the physical properties of the resulting regenerated water-absorbent resin composition, the following substances may be added during preparation of the aqueous monomer solution.

[0086] Specifically, hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salts), and crosslinked polyacrylic acid (salts) can be added in amounts of preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (lower limit: 0% by mass); foaming agents such as carbonates, azo compounds, and bubbles, surfactants, chelating agents, chain transfer agents, etc. can be added in amounts of preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (lower limit: 0% by mass); etc. can be added in amounts of preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (lower limit: 0% by mass).

[0087] When a water-soluble resin or a water-absorbent resin is used as the hydrophilic polymer, a graft polymer or a water-absorbent resin composition (e.g., a starch-acrylic acid polymer, a PVA-acrylic acid polymer, etc.) is obtained. These polymers and water-absorbent resin compositions are also within the scope of the present invention.

[0088] (monomer concentration) The monomer mixture is polymerized in an aqueous solution. The concentration of the monomer mixture is appropriately determined, but is usually selected to be 10% by mass or more and 80% by mass or less, preferably 20% by mass or more and 70% by mass or less, and more preferably 30% by mass or more and 60% by mass or less. The monomer mixture polymerized in an aqueous solution provides a hydrous gel polymer.

[0089] (Addition of solubilizing polymer) When the solubilizing polymer is added in the "process for preparing an aqueous monomer solution", the solubilizing polymer (or its aqueous solution, aqueous dispersion) may be mixed with the aqueous monomer solution, or the solubilizing polymer (or its aqueous solution, aqueous dispersion) may be mixed in advance with water and then mixed with the monomer (or its aqueous solution). From the viewpoint of uniform mixing of the raw materials, it is preferable to mix the solubilizing polymer (or its aqueous solution, aqueous dispersion) with the aqueous monomer solution. When the solubilizing polymer and / or the solubilizing polymer is added as an aqueous solution, it may be added after heating to 50°C or higher.

[0090] (Addition of chelating agent) The performance can be stabilized by further adding a chelating agent to the above monomer, particularly by adding a solubilizing polymer and a chelating agent.

[0091] (2-2) Polymerization process (Polymerization method) The polymerization form applied in the present invention is not particularly limited, but from the viewpoint of water absorption characteristics, ease of polymerization control, etc., preferred examples include spray droplet polymerization, aqueous solution polymerization, and reversed-phase suspension polymerization, more preferred examples are aqueous solution polymerization and reversed-phase suspension polymerization, and even more preferred examples are aqueous solution polymerization. Among these, continuous aqueous solution polymerization is particularly preferred, and either continuous belt polymerization or continuous kneader polymerization can be applied.

[0092] As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Patent Nos. 4,893,999, 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Patent Nos. 6,987,151, 6,710,141, etc. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin is improved.

[0093] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization." "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of the aqueous monomer solution of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination.

[0094] In one embodiment of the present invention, the polymerization can be carried out under an air atmosphere, but from the viewpoint of the color tone of the obtained water absorbent resin, it is preferable to carry out the polymerization under an inert gas atmosphere such as nitrogen or argon. In this case, for example, it is preferable to control the oxygen concentration to 1 volume % or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, dissolved oxygen: less than 1 mg / l).

[0095] In one embodiment of the present invention, the polymerization may be carried out as foaming polymerization in which bubbles (particularly the above-mentioned inert gases or the like) are dispersed in an aqueous monomer solution.

[0096] (Polymerization initiator) The polymerization initiator used in the present invention is not particularly limited since it is appropriately selected depending on the polymerization form, etc., but examples thereof include a thermally decomposable polymerization initiator, a photodecomposable polymerization initiator, or a combination of these, or a redox-based polymerization initiator combined with a reducing agent that promotes the decomposition of the polymerization initiator, etc. Preferably, a peroxide or an azo compound is used, and more preferably, the polymerization of the aqueous monomer solution is carried out with an oxidizing agent, particularly a peroxide or a persulfate, in order to further exert the effects of the present invention.

[0097] When an oxidizing agent is used as a decomposing agent for a water-absorbent resin, particularly when the oxidizing agent is used in polymerization, the effect of the present invention in controlling the amount of residual decomposing agent to a low level is more effectively exhibited, which is preferable.

[0098] The amount of the polymerization initiator used is preferably 0.001 mol % to 1 mol %, more preferably 0.001 mol % to 0.5 mol %, based on the monomer. The amount of the reducing agent used is preferably 0.0001 mol % to 0.02 mol %, based on the monomer.

[0099] (Addition of solubilizing polymer) When the solubilizing polymer is added in the "polymerization step", the solubilizing polymer (or aqueous solution or aqueous dispersion) may be added before or after the start of polymerization. From the viewpoint of uniformity of the polymer component, it is preferable to add the solubilizing polymer before the start of polymerization.

[0100] When the solubilized polymer obtained by the solubilization treatment (decomposition) or its aqueous solution is added, the amount of the oxidizing agent remaining in the solubilized polymer or its aqueous solution may be measured in advance by a method such as redox titration or ion chromatography to determine the content of the oxidizing agent contained in the solubilized polymer, and conditions such as the amount of initiator used in the "polymerization step" (when an oxidizing agent is used as an initiator, the amount of oxidizing agent added in the polymerization step) and the starting temperature may be adjusted based on the amount. In the production of the above-mentioned recycled water absorbent resin composition, a step of adding an oxidizing agent may be further included in a step after the polymerization step. In other words, the amount of oxidizing agent to be added may be determined based on the content of the oxidizing agent contained in the above-mentioned solubilized polymer, and may be used as an initiator used in the polymerization step and / or as an additive to be mixed in a step after the polymerization step.

[0101] (Addition of chelating agent) The performance can be more stabilized by further adding a chelating agent to the above polymerization step, particularly by using both the solubilizing polymer and the chelating agent.

[0102] (2-3) Hydrogel crushing process (optional) (Gel crushing device and particle size) This step is a step of obtaining a particulate hydrogel (hereinafter referred to as "particulate hydrogel") by gel-pulverizing the hydrogel obtained in the polymerization step using, for example, a screw extruder such as a kneader or a meat chopper, or a gel pulverizer such as a cutter mill. When the polymerization step is kneader polymerization, the polymerization step and the gel-pulverizing step are carried out simultaneously. When the particulate hydrogel is obtained directly in the polymerization process, such as in gas-phase polymerization or reversed-phase suspension polymerization, the gel-pulverizing step may not be carried out.

[0103] The hydrogel before drying is preferably hydrogel particles, and the mass average particle size (hereinafter referred to as gel particle size) is 3 mm or less, 2 mm or less, preferably 1 mm or less, 800 μm or less, more preferably 500 μm or less, 400 μm or less. From the viewpoint of effectiveness, the lower limit is about 100 μm. By keeping it within this range, it becomes easy to remove foreign matter by classification (especially removing pulp and fine particles).

[0104] (Addition of solubilizing polymer) When the solubilizing polymer is added in the "gel crushing step", the solubilizing polymer (or aqueous solution or aqueous dispersion) may be added before crushing, or may be added during crushing. It may also be added in portions. From the viewpoint of uniformity of the gel component, it is preferable to add the solubilizing polymer before gel crushing.

[0105] (Addition of chelating agents and / or reducing agents) The performance can be more stabilized by further adding a chelating agent and / or a reducing agent in the above gel crushing step, particularly by using the solubilizing polymer together with the chelating agent and / or the reducing agent.

[0106] (2-4) Drying process (Drying method) This step is a step of obtaining a dried polymer by drying the particulate hydrogel obtained in the above polymerization step and / or hydrogel crushing step to a desired resin solid content. The resin solid content is determined from the loss on drying (the mass change when 1 g of the water-absorbent resin is heated at 180°C for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 99% by mass, even more preferably 90% by mass to 98% by mass, and particularly preferably 92% by mass to 97% by mass. When the resin solid content is within this range, the coloration of the water-absorbent resin after drying can be controlled to be low even if a used water-absorbent resin or a solubilized product thereof is used as a part of the raw material.

[0107] The method for drying the particulate hydrogel is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferred, and band drying in which hot air drying is performed on a ventilation belt is more preferred.

[0108] The drying temperature is preferably from 120° C. to 250° C., more preferably from 150° C. to 200° C., from the viewpoint of the color tone of the water-absorbent resin and drying efficiency, etc. The drying time is preferably from 10 minutes to 120 minutes, more preferably from 20 minutes to 90 minutes, and further preferably from 20 minutes to 60 minutes.

[0109] (Cooling after drying) In order to solve the problems of the present invention, forced cooling is performed after the drying step, particularly cooling to a range of 100° C. or less, 90° C. or less, or 85° C. or less (the lower limit is 40° C. or 50° C.). If cooling is not performed, coloration or aggregation of the water absorbent resin may occur, and further, particle size control during pulverization may be difficult.

[0110] (Addition of solubilizing polymer) When the solubilizing polymer is added in the "drying step", the hydrogel and the solubilizing polymer (or an aqueous solution or dispersion thereof) may be mixed before drying, or they may be dried without being mixed.

[0111] (Addition of chelating agents and / or reducing agents) The performance can be more stabilized by further adding a chelating agent and / or a reducing agent in the above drying step or a step before that, and particularly by having the solubilized polymer and the chelating agent and / or the reducing agent coexist after the drying step.

[0112] (2-5) Grinding process, classification process Preferably, the sizing step includes a pulverization step and / or a classification step. In the pulverization step, the powder is pulverized, and further, foreign matter can be removed by classification.

[0113] From the viewpoint of water absorption performance and removal of foreign matter in classification, the mass average particle diameter of the water absorbent resin obtained through the sieving step is more preferably 200 μm to 600 μm, even more preferably 250 μm to 550 μm, and particularly preferably 300 μm to 500 μm. From the viewpoint of the quality of the obtained recycled water absorbent resin composition, it is preferable that the recycled water absorbent resin composition is mainly composed of particles having a particle diameter of 150 μm to 850 μm as defined by sieve classification. The ratio of particles having a particle diameter of 150 μm to 850 μm in the recycled water absorbent resin composition is preferably 90% by mass to 100% by mass, more preferably 95% by mass to 100% by mass, even more preferably 97% by mass to 100% by mass, and particularly preferably 99% by mass to 100% by mass. Therefore, the proportion of particles having a particle size of less than 150 μm or more than 850 μm as determined by sieve classification is preferably 10 mass % or less, more preferably 5 mass % or less, and even more preferably 3 mass % or less.

[0114] (2-6) Surface crosslinking process (Surface cross-linking agent) This step is a step of adding a surface crosslinking agent that reacts with the functional group (particularly carboxyl group) of the water-absorbent resin to the hydrogel after polymerization or its dried product to cause a crosslinking reaction, and is also called surface crosslinking or secondary crosslinking because crosslinking occurs mainly from the surface of the water-absorbent resin. In the production method according to the present invention, a surface crosslinking agent is added to the water-absorbent resin after the pulverization or classification during or after drying, particularly after drying, to cause a reaction. The method includes a surface crosslinking agent addition step and a heat treatment step, and may include a cooling step after the heat treatment step as necessary.

[0115] As the surface crosslinking agent, a surface crosslinking agent capable of reacting with a plurality of functional groups (preferably a plurality of carboxyl groups) of the water-absorbing resin, preferably a surface crosslinking agent capable of covalent bonding or ionic bonding, further a surface crosslinking agent capable of covalent bonding, is used.Specific examples thereof include polyhydric alcohol compounds such as ethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, 1,3-propanediol, 2-butene-1,4-diol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol; epoxy compounds such as ethylene glycol diglycidyl ether and polyethylene glycol diglycidyl ether; alkylene carbonate compounds such as 1,3-dioxolane-2-one and 4-methyl-1,3-dioxolane-2-one; and the like.

[0116] The amount of the surface cross-linking agent added is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less, based on the solid content of the water absorbent resin during or after drying. The lower limit is preferably 0.001% by mass.

[0117] The surface cross-linking agent may be added as it is, but is preferably added as a solution dissolved in water or an organic solvent from the viewpoint of ease of addition. The concentration of the surface cross-linking agent solution is preferably 1% by mass or more, more preferably 2% by mass or more. The total amount of the solvent selected from water and an organic solvent is preferably 0% by mass or more and 10% by mass or less, more preferably 0.1% by mass or more and 8% by mass or less, and even more preferably 0.5% by mass or more and 5% by mass or less, based on the solid content of the water absorbent resin. When water and an organic solvent are used in combination, it is preferable that water is the main component.

[0118] (Surface crosslinking temperature) The water-absorbent resin containing the surface cross-linking agent is heated to 100°C or higher to obtain a surface-cross-linked water-absorbent resin. The preferred maximum temperature varies depending on the type of surface cross-linking agent, but is 100°C or higher and 250°C or lower, more preferably 120°C or higher and 230°C or lower, and even more preferably 150°C or higher and 210°C or lower. The time of the heat treatment step may be appropriately set based on the water content of the water-absorbent resin, the type of the surface cross-linking agent, the thermal efficiency of the heating device, and the like. As a rough guide, heating may be performed until the water content becomes 10% by mass or lower, and the time is in the range of 10 minutes to 120 minutes, preferably 30 minutes to 90 minutes. After surface cross-linking, the reaction may be stopped by cooling as desired. In the cooling step, the reaction is forcibly cooled, if necessary, to preferably 40°C to 80°C, more preferably 50°C to 70°C.

[0119] (Addition of solubilizing polymer) When the solubilizing polymer is added in the "surface cross-linking step", the solubilizing polymer may be mixed with the water absorbent resin that has been dried in advance. The solubilizing polymer may be dissolved or dispersed in the surface treatment liquid and added to the water absorbent resin. In the case of an aqueous solution of the solubilizing polymer, the amount of water used in the surface treatment liquid is adjusted so that it is 0.1 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the water absorbent resin precursor.

[0120] (Addition of chelating agents and / or reducing agents) The performance can be more stabilized by further adding a chelating agent and / or a reducing agent in the above surface crosslinking step or a step before that, particularly by coexisting a solubilized polymer and a chelating agent and / or a reducing agent in the surface crosslinking step.

[0121] (2-6) Granulation process (fine powder granulation process) When the solubilizing polymer is added in the granulation process, especially in the fine powder granulation process,

[0122] The chelating agent and / or reducing agent can be added, and the solubilizing polymer and the ...

[0123] (2-7) Other processes In the production method according to the present invention, other additives may be added before or after drying, such as inorganic fine particles, dust inhibitors, fungicides, antibacterial agents, antioxidants, ultraviolet absorbers, colorants, fragrances, deodorants, and organic fibrous materials. When these additives are added, the content (mass%) of the additives is preferably 0.001% by mass or more and 10% by mass or less, more preferably 0.01% by mass or more and 5% by mass or less, particularly preferably 0.05% by mass or more and 1% by mass or less, and most preferably 0.1% by mass or more and 0.5% by mass or less, based on the mass of the crosslinked polymer (A). Specific examples of the inorganic fine particles include minerals such as hydrotalcite; silicon oxide, titanium oxide, and aluminum oxide.

[0124] (3) Properties of the recycled water-absorbent resin composition The recycled water-absorbent resin composition obtained above has little coloring or foreign matter, and can be used in a wider range than conventional water-absorbent resins. The recycled water-absorbent resin composition obtained has the following properties:

[0125] The YI value (Yellow-Index) of the recycled water-absorbent resin composition of the present invention is preferably not more than 20, more preferably not more than 15. With this constitution, the recycled water-absorbent resin composition, which is substantially white, can be used in a wider range of applications.

[0126] The residual monomer content of the recycled water absorbent resin composition of the present invention is preferably 300 ppm or less, more preferably 200 ppm or less, and further preferably 100 ppm or less. With such a constitution, the recycled water absorbent resin composition can be used in a wider range of applications, and the by-production of acrylamide can be suppressed.

[0127] The amount of foreign matter (typified by pulp) contained in the recycled water absorbent resin composition of the present invention is preferably 1 mass % or less, more preferably 0.5 mass % or less, and further preferably 0.1 mass % or less.

[0128] The amount of urea and ammonia contained in the recycled water absorbent resin composition of the present invention is preferably 4 mass % or less, more preferably 3 mass % or less, further preferably 2 mass % or less, and particularly preferably 1 mass % or less. With such a constitution, the performance deterioration of the recycled water absorbent resin composition can be suppressed, and it can be used in a wider range.

[0129] The recycled water absorbent resin composition of the present invention has a high water absorption capacity (high CRC) even though it is made of a used water absorbent resin or its solubilized product as a part or all of the raw material. The CRC is preferably 15 g / g or more, more preferably 25 g / g or more. There is no particular restriction on the upper limit, and a higher CRC is preferable, but from the viewpoint of the balance with other physical properties, it is preferably 70 g / g or less, more preferably 50 g / g or less, and even more preferably 40 g / g or less.

[0130] The recycled water absorbent resin composition of the present invention has a high water absorption capacity under pressure (high AAP) even though used water absorbent resin or its solubilized product is used as a part or all of the raw material. The AAP is preferably 15 g / g or more, more preferably 20 g / g or more, even more preferably 22 g / g or more, particularly preferably 23 g / g or more, and most preferably 24 g / g or more. The upper limit is not particularly limited, but is preferably 30 g / g or less.

[0131] The recycled water absorbent resin composition of the present invention has a low water-soluble content, even though it is made of a used water absorbent resin or a solubilized product thereof as a part or all of the raw material. The water-soluble content is usually 50 mass % or less, preferably 35 mass % or less, more preferably 25 mass % or less, and further preferably 15 mass % or less.

[0132] The water content of the recycled water absorbent resin composition of the present invention is preferably more than 0 mass% and not more than 20 mass%, more preferably 1 mass% or more and 15 mass% or less, even more preferably 2 mass% or more and 13 mass% or less, and particularly preferably 2 mass% or more and 10 mass% or less.

[0133] The particle size of the recycled water-absorbent resin composition of the present invention is preferably within the above range.

[0134] (4) Uses of the recycled water-absorbent resin composition The use of the recycled water absorbent resin composition obtained by the present invention is not particularly limited, but it is preferably used as an absorbent material for absorbent articles such as paper diapers, sanitary napkins, incontinence pads, etc. In particular, it can be used as an absorbent material for high-concentration paper diapers, which have been problematic in terms of odor, coloration, etc. derived from raw materials.

[0135] The present invention may also include the following inventions [1] to

[16] . [1] The process includes a polymerization step of an aqueous monomer solution and a drying step of the hydrogel-like cross-linked polymer after polymerization, A method for producing a recycled water-absorbent resin composition, comprising solubilizing 50% by mass or more of a water-absorbent resin with a decomposition agent and using an aqueous solution of the solubilized polymer obtained as a part of a raw material, comprising: The mass average molecular weight (Mw) of the solubilizing polymer is 30,000 or more, and A method for producing a recycled water-absorbent resin composition, wherein the amount of decomposition agent remaining in the aqueous solution of the solubilized polymer is 1000 ppm or less. [2] The process includes a step of polymerizing an aqueous monomer solution and a step of drying the hydrogel-like cross-linked polymer after polymerization, A method for producing a recycled water-absorbent resin composition, comprising solubilizing 50% by mass or more of a water-absorbent resin with a decomposition agent and using an aqueous solution of the solubilized polymer obtained as a part of a raw material, comprising: The method for producing a recycled water-absorbent resin composition, wherein the solubilized polymer has a mass average molecular weight (Mw) of 30,000 or more after a treatment for reducing the amount of decomposing agent remaining in the aqueous solution of the solubilized polymer is carried out. [3] The method according to [1] or [2], wherein the amount of the decomposition agent remaining in the aqueous solution of the solubilized polymer after the reduction treatment is 40 ppm or less. [4] The method according to any one of [1] to [3], wherein the decomposition agent used for solubilizing the water absorbent resin contains an oxidizing agent in an amount of 1000 ppm or more and 10 mass % or less, a reducing agent in an amount of 0 ppm or more and 1000 ppm or less, and a heavy metal in an amount of 0 ppm or more and 10 ppm or less. [5] The method according to any one of [1] to [4], wherein the reduction rate of the decomposition agent remaining in the aqueous solution of the solubilized polymer, as defined by the following formula (a), is 90 mass % or more: (Reduction rate of decomposition agent) (mass%) = (amount of decomposition agent remaining in the aqueous solution of solubilized polymer) / (amount of decomposition agent used for solubilization) × 100 Formula (a) [6] The method according to any one of [1] to [5], wherein the water-absorbent resin is solubilized by heat treatment at 40° C. or higher and 195° C. or lower. [7] The method according to any one of [1] to [6], wherein the water-absorbent resin is solubilized by heat-treating a hydrous gel-like crosslinked polymer having a water-absorbent resin concentration of 1% by mass or more and 90% by mass or less. [8] The method according to any one of [1] to [7], wherein the treatment for reducing the amount of the decomposing agent after solubilization of the water absorbent resin is carried out by aging or storing in a heated state at 40° C. or higher for 10 minutes or more. [9] The method according to any one of [1] to [8], wherein the treatment for reducing the amount of the decomposing agent after solubilization of the water-absorbing resin is carried out by adding an acid or an alkali.

[10] The method according to any one of [1] to [9], wherein the aqueous solution of the solubilized polymer has a temperature of 40° C. or higher.

[11] The method according to any one of [1] to

[10] , wherein the aqueous solution of the solubilized polymer is mixed with an aqueous monomer solution or a hydrous gel-like crosslinked polymer before drying.

[12] The method according to any one of [1] to

[11] , wherein the polymerization of the aqueous monomer solution is carried out in the presence of an oxidizing agent.

[13] The method according to any one of [1] to

[12] , wherein a chelating agent is further mixed into the aqueous solution of the solubilized polymer during or after mixing in the production process of the regenerated water absorbent resin composition.

[14] The method according to any one of [1] to

[13] , wherein a reducing agent is further mixed into the aqueous solution of the solubilized polymer during or after mixing in the production process of the regenerated water absorbent resin composition.

[15] The method according to any one of [1] to

[14] , wherein the water-absorbing resin is a used water-absorbing resin.

[16] The method according to any one of [1] to

[15] , wherein the amount of residual urea in the aqueous solution of the solubilized polymer is 2 mass% or less. EXAMPLES

[0136] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples, and examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention. Unless otherwise noted, measurements were taken at room temperature (20°C or higher and 25°C or lower) and at a relative humidity of 50±5% RH. For convenience, "liter" may be expressed as "l" or "L," and "mass%" may be expressed as "wt%."

[0137] (Measurement and evaluation methods) The methods for measuring and evaluating the various physical properties in the examples and comparative examples are as follows.

[0138] (a) Mass average molecular weight, number average molecular weight, molecular weight distribution (Preparation of measurement samples) The water-absorbing resin (solubilized polymer) was dissolved in the following solvent to prepare a solution with a concentration of 0.1% by mass. The resulting solution was then passed through a filter (GL Sciences: GL Chromatodisk, aqueous 25A, pore size 0.2 μm) to prepare a measurement sample.

[0139] Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH 6.35 to 6.38).

[0140] Using the measurement sample, GPC measurement was carried out under the following measurement conditions. (GPC measurement) The above measurement samples were subjected to GPC measurement using a Viscotec TDAmax manufactured by Malvern Instruments. The measurement device was equipped with a size exclusion chromatograph, a refractive index detector, a light scattering detector, and a capillary viscometer. The measurement device and measurement conditions were as follows. Pump, autosampler: Viscotec GPCmax (Malvern) Guard column: OHpak SB-G (Showa Denko Co., Ltd.) Column: OHpak SB-806MHQ (Showa Denko K.K.), two columns connected in series Detector: Viscotec TDAmax (Malvern) Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH 6.35 to 6.38). Flow rate: 0.5mL / min Injection volume: 100μL. The water used in the GPC measurements was pure water from which impurities had been thoroughly removed. The GPC measurements were performed under conditions where the detector baseline was stable, particularly when there were no noise peaks in the light scattering detector.

[0141] The measuring device was calibrated using polyoxyethylene glycol (mass average molecular weight (Mw): 21966, molecular weight distribution (Mw / Mn): 1.0, differential refractive index (dn / dc): 0.132, solvent refractive index: 1.33) as a standard sample.

[0142] The differential refractive index (dn / dc) of the water-absorbent resin (solubilized polymer) to be measured was set to 0.12, and the solvent refractive index was set to 1.33. Data collection and analysis of the refractive index, light scattering intensity, and viscosity were performed using software (Viscotek OmniSEC4.7.0 (registered trademark)).

[0143] Based on the refractive index (RI), light scattering intensity (angle: 7°) (LALS) and data obtained from the viscometer (DP) obtained in the above measurements, the mass average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the water absorbent resin (solubilized polymer) were calculated.

[0144] (b) Residual amount of hydrogen peroxide The amount of hydrogen peroxide remaining in the aqueous solubilized polymer solution was determined according to the following procedure.

[0145] Specifically, 0.50 g of the solubilized polymer aqueous solution, 8.5 g of industrially pure water, and 1.0 g of a 10% by mass aqueous calcium chloride solution were placed in a container and mixed to precipitate the solubilized polymer, which was then filtered through a 0.2 μm chromatodisc.

[0146] 0.30 g of 1 mol / l (2N) sulfuric acid was added to the obtained filtrate, and after mixing, coloring was performed with 0.10 g of 30 mass % titanium (IV) sulfate.

[0147] The absorbance was measured using a ratio beam spectrophotometer U-5100 (Hitachi High-Tech Corporation) and the attached 10 mm square cell. In addition, industrial pure water was used as the standard. The absorbance at a wavelength of 410 nm was measured using the above spectrophotometer.

[0148] On the other hand, a calibration curve of hydrogen peroxide amount vs. absorbance was created by reacting a calibration sample with known hydrogen peroxide concentration with titanium(IV) sulfate in the same manner. The "amount of hydrogen peroxide remaining in the solubilized polymer aqueous solution" was calculated from the calibration curve.

[0149] (c)CRC The "CRC" of a water-absorbent resin is an abbreviation for "Centrifuge Retention Capacity" and indicates the absorption capacity (unit: g / g) of a water-absorbent resin for 30 minutes under no pressure with respect to a 0.90% by mass aqueous sodium chloride solution. A specific method for measuring the CRC of a water-absorbent resin (recycled water-absorbent resin composition) is as follows.

[0150] 0.200 g of the water-absorbent resin was uniformly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Industrial Co., Ltd., product name: Heatlon Paper, model: GSP-22) and heat-sealed. The bag (containing the water-absorbent resin) was immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes at a centrifugal force (250 G) described in ERT441.2-02 using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122), and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. From the obtained values ​​of W1 and W0, the CRC of the control water-absorbent resin was calculated according to the following formula (1): CRC of absorbent resin (g / g) = (W1-W0) / (mass of absorbent resin)-1···Equation (1).

[0151] (d) AAP0.3 The "AAP" of a water-absorbent resin is an abbreviation for "Absorption Against Pressure" and indicates the absorbency (unit: g / g) against a 0.90% by mass aqueous sodium chloride solution. Also, "AAP0.3" means the AAP under a pressure of 0.3 psi.

[0152] The AAP0.3 of the above water absorbent resin (regenerated water absorbent resin composition) was measured in accordance with ERT442.2-02. Specifically, 0.9 g of the water absorbent resin was placed in a large excess of 0.9 mass % sodium chloride aqueous solution for 1 hour, and the AAP0.3 was measured at 2.07 kPa (21 g / cm 2 The value was measured after swelling under a pressure of 0.5 psi (0.3 psi).

[0153] (e) Color evaluation (yellowness index / YI value) The color evaluation of the water-absorbent resin was performed using a spectrophotometer (Spectrophotometer SE7700) manufactured by Nippon Denshoku Industries Co., Ltd. Reflection measurement was selected as the measurement setting condition, and the measurement diameter was LAV (28 mm). In addition, the attached 35Φ×15H round cell, 35Φ×15H cell case, and standard white board for powder were used. The YI value (Yellow Index) was measured with the above spectrophotometer under the conditions of room temperature (20°C or higher and 25°C or lower) and humidity of 50 RH%.

[0154] (f) Solid content concentration / moisture content A water-absorbent resin (hydrated gel) having a mass Wa (g) was placed on an aluminum plate having a mass Wb (g) and dried in a hot air circulating oven at 180° C. for 3 hours. Thereafter, the total mass Wc (g) of the water-absorbent resin (hydrated gel) and the aluminum plate was measured. From the obtained values ​​of Wa, Wb, and Wc, the solid content concentration of the water-absorbent resin (hydrated gel) was calculated according to the following formula (2): Solids concentration (mass%) of water-absorbent resin (hydrated gel) = {(Wc - Wb) / Wa} × 100 Equation (2).

[0155] The water content of the water-absorbent resin (hydrous gel) is calculated according to the following formula (3): Water content (mass%) of water-absorbent resin (water-containing gel) = 100 – (solids concentration of water-absorbent resin (water-containing gel)) Equation (3).

[0156] [Production Example 1] A reaction vessel was charged with 244.9 g of acrylic acid, 0.71 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 103.7 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 389.0 g of deionized water, and mixed to prepare an aqueous monomer solution (S1').

[0157] Next, the monomer aqueous solution (S1') was cooled while stirring. When the liquid temperature reached 40.0°C, 100.9 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (S1). At this time, the temperature of the monomer aqueous solution (S1) rose to 78.2°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.

[0158] Next, 12.1 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred monomer aqueous solution (S1), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second neutralization to the pouring of the monomer aqueous solution (S1) into the vat-type container was 55 seconds, and the vat-type container was a hot plate, which was heated until the surface temperature reached 40°C after the monomer aqueous solution (S1) was poured. The polymerization reaction started 60 seconds after the monomer aqueous solution (S1) was poured into the vat-type container. The polymerization reaction proceeded with the reactants expanding and foaming in all directions while generating water vapor. After the reaction, the reactants shrunk to a size slightly larger than the vat-type container. Three minutes after the start of the polymerization reaction, the reactants were taken out as a hydrogel-like crosslinked polymer (hereinafter abbreviated as "hydrogel") (S1). The series of operations was carried out in an open-air system.

[0159] The hydrogel (S1) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm. The particulate hydrogel (S1) was then placed on a 50-mesh wire screen and dried with hot air at 190°C for 60 minutes. The dried product was then crushed using a vibration mill. The crushed product was then classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm. This operation yielded an irregularly crushed water-absorbent resin precursor (S1).

[0160] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water was added to 100 parts by mass of the obtained water absorbent resin precursor (S1), and the obtained mixture was mixed. Next, the obtained mixture was heat-treated at 100°C for 45 minutes to perform surface crosslinking of the water absorbent resin precursor (S1), thereby obtaining a water absorbent resin (S1).

[0161] The obtained water absorbent resin (S1) had a CRC of 35.9 g / g, an AAP0.3 of 29.4 g / g, and a YI value (yellowness index) of 10.3.

[0162] Next, 1,800 parts by mass of a 0.9% by mass aqueous sodium chloride solution (physiological saline) was added to 200 parts by mass of the above water absorbent resin (S1), and the mixture was left at room temperature for 8 hours or more to obtain a simulated used water absorbent resin (S1).

[0163] [Production Example 2] 200.0 g of the simulated used water absorbent resin (S1) obtained in Production Example 1 and 1.60 g of a 48.5 mass% aqueous sodium hydroxide solution as a pH adjuster were added to a reaction vessel, and thoroughly mixed with a spatula. Next, 1.33 g of a 30 mass% aqueous hydrogen peroxide solution as a decomposition agent was added for the reaction, and further thoroughly mixed with a spatula. Here, a part of the mixture (1) in the reaction vessel was taken out and attached to a pH test paper, and it was confirmed that the pH of the mixture (1) was 6.5 to 7.0.

[0164] Next, the reaction vessel containing mixture (1) was immersed in a thermostatic bath at 100°C to initiate the decomposition reaction. 45 minutes after immersion, the state of decomposition of mixture (1) was checked using a spatula, and no gel-like matter was observed, and almost all of the mixture had been solubilized. The product obtained by this operation was designated solubilized polymer (S2).

[0165] The pH of the aqueous solution of the solubilized polymer (S2) was measured using a pH meter (LAQUA act D-71 manufactured by Horiba, Ltd.) and found to be 6.93. The solid content of the aqueous solution of the solubilized polymer (S2) was 10.4% by mass, the YI value was 9.2, and the mass average molecular weight Mw was 541,000. The amount of hydrogen peroxide remaining in the aqueous solution was 1650 ppm.

[0166] [Production Example 3] In order to remove hydrogen peroxide remaining in the aqueous solution of solubilized polymer (S2) obtained in Production Example 2, 1.89 g of a 48.5% by mass aqueous solution of sodium hydroxide was added and stirred with a stirrer at 25° C. for 3 hours. After that, the amount of hydrogen peroxide remaining in the aqueous solution of solubilized polymer (S2) was measured and found to be 0 ppm. The solubilized polymer from which hydrogen peroxide had been removed was designated as solubilized polymer (S3).

[0167] [Example 1] A reaction vessel was charged with 220.4 g of acrylic acid, 0.64 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 288.5 g of the solubilized polymer (S3) obtained in Production Example 3, 1.83 g of a 1.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 93.4 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 61.5 g of deionized water, and the mixture was mixed to prepare an aqueous monomer solution (1').

[0168] Next, the monomer aqueous solution (1') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (1). At this time, the temperature of the monomer aqueous solution (1) rose to 78.2°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.

[0169] Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous monomer solution (1), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second neutralization to the pouring of the aqueous monomer solution (1) into the vat-type container was 55 seconds, and the vat-type container was a hot plate, which was heated until the surface temperature reached 40°C after the aqueous monomer solution (1) was poured. The polymerization reaction started 70 seconds after the aqueous monomer solution (1) was poured into the vat-type container. The polymerization reaction proceeded while the reactants expanded and foamed in all directions while generating water vapor. After the reaction, the reactants contracted to a size slightly larger than the vat-type container. After 3 minutes had passed since the start of the polymerization reaction, the reactants were taken out as a hydrogel-like crosslinked polymer (hereinafter abbreviated as "hydrogel") (1). The series of operations was carried out in an open-air system.

[0170] The hydrogel (1) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm. The particulate hydrogel (1) was then placed on a 50-mesh wire screen and dried with hot air at 190°C for 60 minutes. The dried product was then crushed using a vibration mill. The crushed product was then classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm. By this operation, an irregularly crushed water-absorbent resin precursor (1) was obtained.

[0171] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water was added to 100 parts by mass of the obtained water absorbent resin precursor (1), and the obtained mixture was mixed. Next, the obtained mixture was heat-treated at 100°C for 45 minutes to perform surface crosslinking of the water absorbent resin precursor (1), thereby obtaining a recycled water absorbent resin composition (1).

[0172] [Comparative Example 1] The same procedure as in Example 1 was carried out except that the solubilized polymer (S2) obtained in Production Example 2 was used instead of the solubilized polymer (S3) in Example 1, to obtain a recycled water absorbent resin composition (C1).

[0173] (Stability evaluation) The operations of Example 1 and Comparative Example 1 were each repeated 10 times. The stability of the monomer during polymerization and the fluctuation of the polymerization time were confirmed. The results are shown in Table 1.

[0174] [Table 1]

[0175] (summary) Comparison between Example 1 and Comparative Example 1 (Table 1) shows that the stability of the monomer during polymerization is improved by controlling the residual decomposition agent in the solubilized polymer to a low level. By improving the stability of the monomer during polymerization, thickening of the aqueous monomer solution does not occur before the addition of the polymerization initiator, and the polymerization initiator can be mixed uniformly, so that the polymerization time is stable (fluctuations are reduced). Therefore, according to the method of the present invention, it is possible to provide a water-absorbing resin with stable physical properties and stable production and with little coloring. [Industrial Applicability]

[0176] The method of the present invention can provide a water absorbent resin having stable physical properties and production and little coloring while using a decomposition product of a used water absorbent resin as a part of a raw material, and therefore contributes to the environment and resource saving and expands the possibility of recycling the water absorbent resin.

Claims

1. The method includes a step of polymerizing an aqueous monomer solution and a step of drying the hydrogel-like crosslinked polymer after polymerization, A method for producing a recycled water-absorbent resin composition, comprising the steps of: solubilizing 50% by mass or more of a water-absorbent resin with a decomposition agent; and using an aqueous solution of the solubilized polymer obtained as a part of a raw material, comprising: The solubilizing polymer has a mass average molecular weight (Mw) of 30,000 or more; and The method for producing a recycled water-absorbent resin composition, wherein the amount of the decomposition agent remaining in the aqueous solution of the solubilized polymer is 1000 ppm or less.

2. The method includes a step of polymerizing an aqueous monomer solution and a step of drying the hydrogel-like crosslinked polymer after polymerization, A method for producing a recycled water-absorbent resin composition, comprising the steps of: solubilizing 50% by mass or more of a water-absorbent resin with a decomposition agent; and using an aqueous solution of the solubilized polymer obtained as a part of a raw material, comprising: The method for producing a regenerated water-absorbent resin composition, wherein the solubilized polymer has a mass average molecular weight (Mw) of 30,000 or more after the treatment for reducing the amount of decomposing agent remaining in the aqueous solution of the solubilized polymer is carried out.

3. 3. The method according to claim 1, wherein the amount of the decomposing agent remaining in the aqueous solution of the solubilized polymer after the reduction treatment is 40 ppm or less.

4. The decomposition agent used for solubilizing the water absorbent resin contains an oxidizing agent in an amount of 1000 ppm or more and 10 mass % or less, a reducing agent in an amount of 0 ppm or more and 1000 ppm or less, and a heavy metal in an amount of 0 ppm or more and 10 ppm or less. The manufacturing method according to claim 1 or 2.

5. The method according to claim 1 or 2, wherein a reduction rate of the decomposition agent remaining in the aqueous solution of the solubilized polymer, as defined by the following formula (a), is 90 mass % or more: (Decomposition agent reduction rate) (mass %)=(amount of decomposition agent remaining in the aqueous solution of solubilized polymer) / (amount of decomposition agent used for solubilization)×100 (Equation (a))

6. The method according to claim 1 or 2, wherein the water-absorbent resin is solubilized by heat treatment at 40° C. or higher and 195° C. or lower.

7. The method according to claim 1 or 2, wherein the water-absorbent resin is solubilized by heat-treating a hydrogel crosslinked polymer having a water-absorbent resin concentration of 1% by mass or more and 90% by mass or less.

8. 3. The method according to claim 1, wherein the treatment for reducing the amount of the decomposing agent after solubilization of the water absorbent resin is carried out by aging or storing the resin in a heated state at 40° C. or higher for 10 minutes or longer.

9. The method according to claim 1 or 2, wherein the treatment for reducing the amount of the decomposing agent after solubilization of the water-absorbent resin is carried out by adding an acid or an alkali.

10. The method according to claim 1 or 2, wherein the aqueous solution of the solubilizing polymer has a temperature of 40° C. or higher.

11. The method according to claim 1 or 2, wherein the aqueous solution of the solubilized polymer is mixed with an aqueous monomer solution or a hydrogel-like crosslinked polymer before drying.

12. 3. The method according to claim 1, wherein the polymerization of the aqueous monomer solution is carried out in the presence of an oxidizing agent.

13. The method according to claim 1 or 2, wherein a chelating agent is further mixed with the aqueous solution of the solubilized polymer during or after mixing in the production process of the regenerated water-absorbent resin composition.

14. The method according to claim 1 or 2, wherein a reducing agent is further mixed with the aqueous solution of the solubilized polymer during or after mixing in the production process of the regenerated water-absorbent resin composition.

15. The method according to claim 1 or 2, wherein the water-absorbing resin is a used water-absorbing resin.

16. The method according to claim 1 or 2, wherein the amount of residual urea in the aqueous solution of the solubilized polymer is 2% by mass or less.

Citation Information

Patent Citations

  • Method for producing water-absorbing resin composition

    JP2023038963A

  • Method and system for recovering pulp fibers and highly water-absorbent polymer from used absorbent articles

    WO2019087485A1

  • Method for regenerating highly water-absorbing polymer, method for producing highly water-absorbing recycled polymer, and use of alkali metal ion source

    WO2019151538A1

  • Method for producing water-absorbing resin particles

    WO2020213298A1

  • Method for recycling superabsorbent polymer derived from used absorbent article and recycled superabsorbent polymer derived from used absorbent article

    WO2020241025A1